Over-expression of miR-101 alleviates ventricular remodelingin rat models with acute myocardial infarction by inhibiting JAK2/STAT3 signaling - WU Bo, GUO Hao, ZHONG Zhao, LIU Junfang, WANG Qi, GUO Jibo (Jichu yixue yu linchuang)
Objective To explore the effect and underlying molecular mechanism of miR-101 on ventricular remodeling in rats after acute myocardial infarction (AMI). Methods The AMI rat model was established using the left anterior descending coronary artery ligation method. The AMI rats were randomly divided into AMI group, agomir-NC group, miR-101 agomir group and coumermycin A1 group, another 12 rats were selected as sham group with 12in each . The targeting relationship between miR-101 and JAK2 was analyzed by Target Scan 8.0 database and double luciferase reporter gene assay. The expression of miR-101 in rat myocardium was detected by RT-qPCR. LVESD, LVEDD, LVEF and LVFS were measured by ultrasonography. The level of IL-1β, IL-6 and TNF-α in rats serum was determined by ELISA. The myocardial tissue lesion and fibrosis were detected by HE staining and Masson staining. The expression of collagenⅠ and TGF-β in rat myocardial tissue was detected by immunohistochemical staining. The expression of E-cadherin, N-cadherin, Vimentin, p-JAK2, JAK2, p-STAT3 and STAT3 proteins was detected by Western blot. Results Compared with AMI group and agomir-NC group, the myocardial tissue lesions and fibrotic area in miR-101 agomir group were significantly decreased(P＜0.05), the level of LVESD, LVEDD, L-1β, IL-6, TNF-α, collagenⅠ, TGF-β, N-cadherin, vimentin, p-JAK2 and p-STAT3 decreased (P＜0.05). The levels of miR-101, LVEF, LVFS and E-cadherin were increased (P＜0.05). Compared with miR-101 agomir group, the myocardial tissue lesions and fibrotic area in coumermycin A1 group significantly increased (P＜0.05), the level of LVESD, LVEDD, L-1β, IL-6, TNF-α, collagenⅠ, TGF-β, N-cadherin, vimentin, p-JAK2 and p-STAT3 was increased (P＜0.05). The level of miR-101, LVEF, LVFS and E-cadherin was decreased(P＜0.05). Conclusions miR-101 inhibits myocardial inflammatory lesions, myocardial fibrosis and epithelial-mesenchymal fransition(EMT) process after AMI with a mechanism targeting at JAK2/STAT3 signaling pathway, thus alleviates ventricular remodeling in rats after AMI.